LINFOMA MEDIASTÍNICO EM UM FELINO - Martins, Tomás De Bitencourt; Grün, Luana; Dos Santos, Jennifer Lavinia Lima; Inkelmann, Maria Andréia (Salão do Conhecimento, 2019)
Projeto de Pesquisa: Causas de morte e razões para eutanásia em animais